Healthy Eating Index-2015 in relation to risk of metabolic dysfunction-associated fatty liver disease among US population: National Health and Nutrition Examination Survey 2017–2018 - Zhang, Wei; Wang, Xinyue; Huang, Jiale; Wang, Siyi; Yao, Qing; Li, Hongwei (Frontiers in Nutrition, 2023)
Background: Metabolic dysfunction‑associated fatty liver disease (MAFLD) is a serious chronic disease in the US. Dietary patterns provide good guidance for the prevention of chronic diseases. The Healthy Eating Index (HEI-2015) is a dietary pattern based on the dietary characteristics of the US. Objective: Since the relation between HEI-2015 and MAFLD is unclear, this study examined their associations using the US National Health and Nutrition Examination Surveys (NHAENS) during 2017-2018. Methods: This study included data of 4062 participants aged ≥20years, without viral hepatitis, or pregnancy. MAFLD is defined as hepatic steatosis with one or more of the following: (1) overweight or obesity (body mass index ≥25 kg/m2); (2) type 2 diabetes; or (3) two or more other metabolic risk abnormalities. HEI-2015 scores were calculated from food intake information collected by the 24-hour meal review method. The relationship of HEI-2015 with MAFLD was calculated using survey-weighted logistic regression analysis after adjusting sex, age, race, education level, smoking status, alcohol use, levels of C- reactive protein, aspartate Aminotransferase, alanine Aminotransferase, a body shape index, minutes of sedentary activity, levels of cholesterol and glucose, energy take, drugs use, hypertension, and diabetes. Results: When compared to the study population with no-MAFLD, the patients with MAFLD showed a lower weighted mean HEI (48.0±0.6). HEI-2015 was inversely associated with MAFLD in the fully adjusted model (Q4 vs Q1, OR = 0.567 (0.407–0.790), P=-0.002). Among the 13 HEI-2015 components, total vegetables, greens and beans, total fruits, whole fruits, whole grainswere negatively associated with MAFLD, while added sugars were positively associated with MAFLD. This inverse association was consistent in subgroups of the participants stratified by sex, age, education level, race, a body shape index, minutes sedentary activity, hypertension, and diabetes. Conclusions: A higher HEI-2015 is associated with a lowered risk of MAFLD which is more obvious among participations who were females, young, Mexican Americans, with higher education, and with no hypertension or diabetes.